The Role Of Psychology In Overcoming Student Borneo In Learning - Imelda Jaslene (International Journal of Multidisciplinary Sciences, 2023)
This study aims to see the role of psychology in overcoming student saturation in learning. Learning is an activity carried out by an individual every day, but in learning, various problems are often found in the process of changing behavior. One of them is the feeling of boredom that is experienced when carrying out the learning process. The method used in this research is qualitative research with library research. The results showed that the problem of learning saturation experienced by students was one of the obstacles that made the quality of student learning outcomes low. Factors causing boredom in learning include the lack of motivation in the learning process, the low creativity of the teacher in presenting interesting material in the learning process. So that this does not become a disturbance in the student learning process, the role of psychology is used in overcoming the saturation experienced by students in learning.